Biomechanical Properties and Mechanotransduction of Skeletal Muscles as The Basis for The Use of Myofascial Osteopathic Techniques - Novoseltsev, S. V.; Reshetnikov, A. G.; Vyunov, V. D.; Suleymanov, T. R.; Nefedova, A. M.; Solomatov, P. G.; Taranenko, S. I.; Kryazheva, A. M.; Moskvicheva, . V. (International Journal of Membrane Science and Technology, 2023)
Skeletal muscles are an important link in human biomechanics. Every movement depends on muscle strength and is important for maintaining health and quality of life. Mechanical loads on the human body directly depend on the state of muscle tissue, so it is necessary to understand the cellular composition and regulation of the tissue responsible for the processes of mechanotransduction . This, in turn, makes it possible to develop methods of effective manual intervention in complex rehabilitation for patients with dysfunctions of the musculoskeletal system. This review describes the molecular basis of mechanotransduction in muscle tissue.